Characterization of Ultralow‐Density Cellular Solids: Lessons from 30 years of Bone Biomechanics Research. Issue 7 (7th April 2021) - Sacher, Sara; Hernandez, Christopher J; Donnelly, Eve
Abstract : Advances in additive manufacturing techniques have enabled the development of microarchitectured materials displaying a combination of low‐density and lightweight structures with high specific strength and toughness. The mechanical performance of microarchitectured materials can be assessed using standard techniques; however, when studying low‐ and ultralow‐density microarchitectured materials, standard characterization techniques can be subject to experimental artifacts. In addition, quantitative assessment and comparisons of microarchitectures with distinct lattice patterns are not always straightforward. Cancellous bone is a natural, ultralow‐density (porosity often exceeding 90%), irregular, cellular solid that has been thoroughly characterized in terms of microarchitecture and mechanical performance over the past 30 years. However, most of the literature on cancellous bone mechanical properties and microstructure–function relationships is in the medical literature and is not immediately accessible to materials designers. Herein, a brief review of state‐of‐the‐art approaches for characterizing the microarchitecture and mechanical performance of ultralow‐density cancellous bone is provided, including methods of addressing experimental artifacts during mechanical characterization of ultralow‐density cellular solids, methods of quantifying microarchitecture, and currently understood structure–function relationships. Abstract : Cancellous bone is a naturally occurring, ultralow‐density, microarchitectured material. Conventional characterization techniques for low‐density microarchitectured materials are susceptible to experimental artifacts that critically influence interpretation. Herein, the methods developed in the bone community are detailed, such as specimen preparation and computational models, that can be applied to the microarchitectured materials field.